2022
DOI: 10.1177/00332941221100445
|View full text |Cite
|
Sign up to set email alerts
|

Positive Schemas: Replication, Associations With Negative Schemas, and the Dark Triad

Abstract: The purpose of the current study was to replicate the factor structure of the 14 positive schemas identified in the earlier study by Louis et al. (2018). Using confirmatory factor analysis (CFA), and Multi-group CFA, the 14 positive schemas were found to be robust across four new non-clinical English-speaking community samples – USA ( n = 396), South Africa ( n = 390), Nigeria ( n = 364), and India ( n = 306). Further, results from CFA, and chi square tests showed that positive and negative schemas were indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…These categories of core emotional needs were labeled as Connection and Acceptance, Healthy Autonomy and Performance, Healthy Limits, and Healthy Standards and Reciprocity. The four categories of core emotional needs and toxic experiences were correlated with each other, and results showed that their effect sizes were way below 0.60, demonstrating support for their independence, as demonstrated earlier by Louis et al [48].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…These categories of core emotional needs were labeled as Connection and Acceptance, Healthy Autonomy and Performance, Healthy Limits, and Healthy Standards and Reciprocity. The four categories of core emotional needs and toxic experiences were correlated with each other, and results showed that their effect sizes were way below 0.60, demonstrating support for their independence, as demonstrated earlier by Louis et al [48].…”
Section: Discussionsupporting
confidence: 76%
“…It is important to note that both these experiences are related to each other in that an increase in one will cause a decrease in the other, but not to the same degree. Both constructs are separate though related to each other, as shown by Louis et al [48] and this study. Meeting these core emotional needs does not automatically lead to a reduction in toxic experiences to the same degree.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations